Mulberry Leaf Flavonoids Improve Milk Production, Antioxidant, and Metabolic Status of Water Buffaloes - Li, Mengwei; Hassan, Faiz-ul; Tang, Zhenhua; Peng, Lijuan; Liang, Xin; Li, Lili; Peng, Kaiping; Xie, Fang; Yang, Chengjian (Frontiers in Veterinary Science, 2020)
This study was aimed to evaluate the effect of mulberry leaf flavonoids (MLF) on oxidative stress, metabolic hormones, and milk production in Murrah buffaloes. Forty multiparous Murrah buffaloes (4±1 lactations) with similar body weight (average 600±50Kg) and stage of lactation (90±20d) were randomly selected for this trial. Four treatment groups (10 buffaloes per group) with different doses of MLF included; control (0g/d), MLF15 (15g/d), MLF30 (30g/d), and MLF45 (45g/d). Buffaloes were fed with total mix ration consisting of grass (Pennisetum purpureum schum), brewery’s grain and concentrate mixture for five weeks. Meteorological data including ambient temperature and relative humidity were recorded using the online dust monitoring system to calculate temperature-humidity index (THI). After one week of adaptation, milk yield was recorded daily while physiological parameters (respiratory rate, rectal, and body surface temperature), and milk composition were measured weekly. At the end of the trial, blood samples were collected to analyze serum metabolic hormones including estradiol (E2), growth hormone (GH), prolactin (PRL), Tri-iodothyronine (T3) and Thyroxine (T4). Moreover, serum heat shock proteins (HSP), antioxidants enzymes including malondialdehyde (MDA), total antioxidant capacity (T-AOC), superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidase (GSH-Px) and blood biochemical indices were also analyzed. Results revealed a decrease (P=0.012) in serum MDA level while increasing (P <0.01) the HSP and serum GHS-Px contents in supplemented buffaloes. Treatment showed a linear and quadratic decrease (p=0.001) in the serum T-AOC while reducing CAT contents linearly (p=0.012) as compared to the control. However, no effect of treatment on serum SOD content was observed. Treatment resulted a linear increase (p=0.001) in serum GH and PRL hormones while increasing serum E2 levels linearly (p=0) and quadratically (P=0.025). Treatment increased (p=0.038) the daily milk yield as compared to the control. However, increase (P < 0.05) in serum T3 and T4 contents, fat corrected milk (4%) and milk protein (%) was observed only in MLF45. Moreover, we observed no change in serum biochemical indices except insulin which linearly increased (p=0.002) in MLF45. Our findings indicated that MLF at 45g per day is an appropriate level to enhance milk performance and alleviate heat stress in buffaloes.